2011
DOI: 10.1128/aem.00691-11
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and Bioaugmentation of an Estradiol-Degrading Bacterium and Its Integration into a Mature Biofilm

Abstract: Bioaugmentation can alter the potential activity as well as the composition of the naturally occurring microbial biota during bioremediation of a contaminated site. The focus of the current study is the pollutant 17␤-estradiol (E2), which can cause endocrine effects and is potentially harmful to aquatic biota and to public health. The community composition and function of biofilms, originating from a wetland system, as affected by augmentation of an estradiol-degrading bacterium (EDB-LI1) under different condi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
32
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 52 publications
(32 citation statements)
references
References 47 publications
(51 reference statements)
0
32
0
Order By: Relevance
“…In all re-inoculation tests, the most significant enhancements in copper extractions were observed for 'Lf-1/1', 'Lf-1/3' and in a less extent 'Ac-1/1' systems. Advantages by microbial re-inoculation at the early stage could be summarized by the following principles (El Fantroussi and Agathos, 2005;Iasur-Kruh et al, 2011): (1) In contrast to re-inoculation at the middle stage (Fig. 7), a higher level of the re-inoculated strain survived and/or grew in the bioleaching environment after re-inoculation at the early stage (Fig.…”
Section: Global Performance Of Re-inoculation Strategies For Enhancinmentioning
confidence: 99%
See 1 more Smart Citation
“…In all re-inoculation tests, the most significant enhancements in copper extractions were observed for 'Lf-1/1', 'Lf-1/3' and in a less extent 'Ac-1/1' systems. Advantages by microbial re-inoculation at the early stage could be summarized by the following principles (El Fantroussi and Agathos, 2005;Iasur-Kruh et al, 2011): (1) In contrast to re-inoculation at the middle stage (Fig. 7), a higher level of the re-inoculated strain survived and/or grew in the bioleaching environment after re-inoculation at the early stage (Fig.…”
Section: Global Performance Of Re-inoculation Strategies For Enhancinmentioning
confidence: 99%
“…The operation of re-inoculation is to re-add pre-grown specific indigenous or allochthonous wild type cultures into a bio-treatment system to improve the catabolism of specific compounds, e.g. diesel oil in the contaminated soil, 17β-estradiol in wastewater, or some pharmaceuticals from sewage sludge (Bento et al, 2005;Iasur-Kruh et al, 2011;Rodríguez-Rodríguez et al, 2014). Some previous studies have indicated that the re-inoculation of biomass enhanced the removal of toxic or recalcitrant compounds as well as changed the composition of the naturally occurring microbial biota in a system (Iasur-Kruh et al, 2011;Wen et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…The cooperative interaction between the residents of the mixed biofilm provided a protection against the invasion by P. tunicata, as well as the diffusion of antimicrobial agents (Burmølle et al, 2006). In wetland ponds, the amount of nutrients supplied determined the effectiveness of invasion by promoting coexistence of species, including an introduced allochthonous estradiol-degrading bacterium which increased the removal of estradiol from the systems (Iasur-Kruh et al, 2011). Yet, perturbations (i.e.…”
Section: Introductionmentioning
confidence: 97%
“…The ability of an invader to adhere and clolonise the native communities has a pivotal role (Russo et al, 2015), but the true drivers of the success of invasion seem to be related to the characteristics of the resident community, such as diversity and evenness, competition for resources, as well as changes in environmental conditions (van Elsas et al, 2012;Iasur-Kruh et al, 2011;Burmølle et al, 2006;Guillier et al, 2008;Mejlholm and Dalgaard, 2007;Zhao et al, 2006). A negative correlation between soil microbial diversity and the survival of Escherichia coli O157:H7 was reported by van Elsas et al (2012).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation